Linking organisational life cycle models to church’s dual nature for effective management - Osward Sichula; Patrick Nanthambwe; Vhumani Magezi (Theologia Viatorum)
A comprehensive understanding of the church’s dual nature is essential for effective governance and management. Traditionally, the church has been viewed through dichotomous lenses as either a purely spiritual organism or a physical organisation, often leading to gaps in management practices. This article addresses the critical question: how can the church’s spiritual and physical dimensions be effectively integrated into governance and management practices, particularly for newly established and growing churches? The article aims to propose a dual perspective for conceptualising the church as both a spiritual and physical entity to improve its governance and management. By linking Organisational Life Cycle models to the physical nature of the church, the study argues for practical strategies to enhance governance, optimise resource allocation and refine management practices. The article employs a systematic literature review to analyse existing perspectives, identify gaps and propose a comprehensive framework for integrating the church’s dual nature. The findings highlight the importance of balancing the church’s spiritual ethos with its organisational structure, addressing critical gaps in governance and management practices caused by one-sided conceptualisations. This framework provides practical insights for church leaders and administrators, ensuring that the church remains true to its spiritual mission while achieving effective organisational management.